In-situ Electrochemical Synthesis of Core-shell Structural NbC@Nb5Si3/Nb Composites in Molten Salt. Issue 3 (March 2021) - Li, Hongmei; Nong, Zhisheng; Xu, Qian; Song, Qiushi; Chen, Ying; Man, Tiannan; Hao, Chenguang
Abstract: Core-shell structural NbC@Nb5 Si3 /Nb composites were synthesized from Nb2 O5, SiO2 and carbon in molten CaCl2 -NaCl salt by electrochemical reduction. Carbon combined with the reduced metal niobium to form NbC core with a diameter of 40nm, and Nb5 Si3 /Nb as the metal shell. A strong bonding between NbC and Nb5 Si3 /Nb is benefit for the in-situ compound. The addition of NbC phase could improve the room temperature fracture resistance and reserve the high temperature strength of Nb5 Si3 /Nb. In order to better understand the reaction mechanism of the electro-deoxidation process, partially reduced samples were obtained by interrupting the reduction process after different reaction times, and examined by XRD, SEM with EDS and TEM analyses.